Epidemiology and temporal trends of childhood type 1 diabetes in China: an analysis of the GBD 2021 - Jin, Feng; Xie, Limin; Wang, Guocheng; Pan, Yu; Wang, Cuijia; Li, Wei (Frontiers in Endocrinology, 2025)
ObjectiveThis study investigates the epidemiological trends of childhood type 1 diabetes (T1D) in China and establishes predictive models to estimate future disease burden.MethodsTemporal trend analyses were performed using data from the Global Burden of Disease (GBD) database, stratified by age and sex. Joinpoint regression analysis was applied to evaluate changes in incidence and mortality rates from 1990 to 2021, complemented by autoregressive integrated moving average (ARIMA) and exponential smoothing state space (ETS) models to project disease trends through 2040.ResultsThe results indicate a rising trend in the incidence of childhood T1D among Chinese children aged 0-14 years, alongside an overall decline in mortality, reflecting an epidemiological pattern characterized by low incidence yet non-negligible mortality. Notably, infants < 1 year of age have shown increasing mortality rates in recent years. Projections indicate that both incidence and mortality in this age group will continue to increase through 2040. Additionally, incidence among children 1 year of age also expected to persist on an upward trajectory. Sex-based disparities were evident, with girls bearing a higher disease burden than boys, as indicated by elevated incidence, mortality and underdiagnosis rates.ConclusionThese findings necessitate enhanced public health and clinical management strategies for childhood T1D in China, specifically targeting underdiagnosis reduction, incidence rate stabilization, and mortality rate improvement.